The Role of Dharma Wanita Sahabat Kampus in Creating a Sexual Violence-Free Campus Environment - Dalimunthe, Ritha F; Siregar, Hairani; Zahro, Azizatuz; Nauly, Meutia; Ramadani; Putra, Rizky (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
This service discusses the strategic role of Dharma Wanita Sahabat Kampus (DWP) and the Task Force for the Prevention and Handling of Sexual Violence (Satgas PPKS) in addressing sexual violence within the University of North Sumatra (USU). DWP USU plays a key role in socialization, training, and advocacy to create a safe and supportive campus culture. The USU PPKS Task Force, through socialization and education activities, aims to raise awareness and involve the entire campus community in the prevention and handling of sexual violence. Data shows that sexual violence at USU, especially between lecturers and students, requires concrete action. The socialization of DWP and PPKS Task Force covers aspects of definition, impact, reporting procedures, and the role of ASN wives in supporting policy implementation. Through this collaboration, it is hoped that a campus environment free of sexual violence will be established and empower the entire academic community. This journal details the concrete steps, embracing the active participation of DWP, PPKS Task Force, and other campus elements to achieve these goals.